Howler monkey tolerance to habitat shrinking: Lifetime warranty or death sentence?. Issue 4 (7th January 2020) - Bicca‐Marques, Júlio César; Chaves, Óscar M.; Hass, Gabriela Pacheco
Abstract: Habitat loss and fragmentation are major threats to the conservation of nonhuman primates. Given that species differ in their responses to fragmented landscapes, identifying the factors that enable them to cope with altered environments or that cause their extirpation is critical to design conservation management strategies. Howler monkeys ( Alouatta spp.) are good models for studying the strategies of tolerant arboreal taxa and how they cope with spatial restriction, because they live in habitats ranging from vast pristine forests to small disturbed fragments and orchards. While some aspects of their ecology and behavior are conserved, others vary in predictable ways in response to habitat shrinking and decreasing resource availability. We argue that the ability of individual howler monkeys to inhabit low‐quality environments does not guarantee the long‐term persistence of the small populations that live under these conditions. Their local extirpation explains why few forest fragments below a given area threshold are frequently inhabited in landscapes where recolonization and gene flow are compromised by long isolation distances or less permeable matrices. In sum, howlers' ability to cope with habitat restriction at the individual level in the short‐term may mask the inevitable fate of isolated populations, thereby compromising the persistence of the species at a regional scale in the long‐term if howlers' need for protection in large forests is undervalued. Abstract : Research Highlights: The ability to cope with habitat shrinking reduces a taxon's risk of extinction in fragmented landscapes in the short‐term. Small and isolated habitat patches cannot support self‐sustaining populations in the long‐term. It is necessary to integrate individual‐ and population‐level responses to habitat shrinking to optimize conservation decisions.